Technological Competitiveness in an International Arena. - Howells, J; Michie, J (CBR (University of Cambridge), 1997)
We suggest three elements to technological globalisation. First, there is the geographical extent in terms of the spatial spread and intensity (or 'depth') of the globalisation of technology. Secondly, there are sectoral variations in the degree of technological globalisation. Lastly, there is the issue of the temporal extent of the globalisation of technology. We analyse global technological competitiveness within this framework, exploring the policy implications for supranational, national, and regional policy-makers, and discuss in particular what key ingredients national governments should focus on to create a successful environment for growth in a